2022
DOI: 10.3389/fenvs.2022.979922
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution decreases the stability of microbial co-occurrence networks in the rhizosphere of native plants

Abstract: Soil microorganisms play an important role in maintaining soil quality and function, although the response of soil microbial biodiversity to heavy metals has been extensively investigated, the microbe-microbe associations under the influence of both native plant species and extremely high heavy metal contamination are not well documented. We examined the diversity and composition of microbial communities and the physicochemical properties in the rhizosphere of three native plant species, Carex breviculmis, Bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 59 publications
2
0
0
Order By: Relevance
“…The findings indicate that the HB and HY treatments exhibit greater network complexity (more nodes and edges) compared to the other treatments, potentially due to increased resource constraints (reduction of carbon and nutrients), thereby enhancing the network complexity of microorganisms. This aligns with previous studies that found microorganisms strengthen connections among themselves to form more complex networks for improved growth in relatively nutrient‐poor soils (Faust & Raes, 2012; Sun et al., 2022). The number of positive and negative junctions reflects the intensity of potential cooperation and competition among microbial communities, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The findings indicate that the HB and HY treatments exhibit greater network complexity (more nodes and edges) compared to the other treatments, potentially due to increased resource constraints (reduction of carbon and nutrients), thereby enhancing the network complexity of microorganisms. This aligns with previous studies that found microorganisms strengthen connections among themselves to form more complex networks for improved growth in relatively nutrient‐poor soils (Faust & Raes, 2012; Sun et al., 2022). The number of positive and negative junctions reflects the intensity of potential cooperation and competition among microbial communities, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that environmental stressors, such as HM contamination, signi cantly in uence endophytic community dynamics, leading to changes in both diversity and abundance. This nding aligns with the research by Sun, Wu [19], which showed that HM, like copper (Cu), plays a crucial role in shaping fungal diversity in contaminated environments. Our ndings corroborated those of the study of Xie, Fan [20], which demonstrated that HM pollution causes changes in the makeup of microbial communities.…”
Section: Discussionsupporting
confidence: 91%